BASQUE LANGUAGE AND BASQUE TOPONYMY: INTERCULTURAL CONTACTS AND STANDARTISATION - Chesnokova, O.S.; Dzhishkariani, L.M. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The Basque language (euskera) is an isolate language spoken by about one million people in northeast Spain and southwest France. According to the most common version about its origin the Basque language is of Aquitanian origin. The aim of this article - to study the modern Basque toponymy, to outline its space and boundaries, to consider its current state in Spain in the light of contacts with the Spanish language applying the methods of onomastic and linguocultural research. An important feature of modern Basque toponymy in Spain is the existence of double names (Basque and Spanish), reflecting the centuries-old contacts of the Basque and Spanish languages. Double names are in the process of standardization in the framework of state policy, and the unification of the literary standard Basque language (euskara batua). Language consciousness of modern Basque population preserves the original Basque toponymy as an essential part of national heritage, although in some cases the Spanish toponyms are preferred to the Basque ones (Bilbao, not Bilbo, for example).